(untitled) (Journal of Science Foundation, 2020)
Background: Haematoma volume is an important issue for the management of spontaneous supratentorial intracerebral hemorrhage patients. Objective: The purpose of the present study was to correlate the Glasgow outcome scale (GOS) and haematoma volume during surgical and conservative management of spontaneous supratentorial intracerebral hemorrhage patients. Methodology: This randomized control trial which was conducted in the Department of Neurosurgery at Dhaka Medical College and Hospital from January 2010 to October 2011 for a period of one year and ten months. All hypertensive patients with spontaneous supratentorial intracerebral hemorrhage who were admitted within 48 hours of stroke in Neurosurgery Department during the study period were considered as a study population. Patients underwent surgery was considered as group I and patients those who did not give the consent for operation were treated conservatively was considered as group II. Surgery and conservative groups were matched in age, GCS, GOS, hematoma location and volume of hematoma. Result: A total of 31 patients were enrolled in this study of which 14 patients underwent surgical evacuation and 17 cases were selected for conservative therapy. Significant negative correlation was found between GCS on admission with hematoma volume in surgery group (r=-0.631; P=0.016) and conservative group (r=- 0.854; p=0.001). A negative but not significant correlation (r=-0.426; P=0.129) between GOS with hematoma volume in group I, where negative significant correlation (r=-0.503; P=0.039) in conservative group II. Conclusion: In conclusion Glasgow outcome scale (GOS) is positively correlated with the haematoma volume during surgical and conservative management of spontaneous supratentorial intracerebral hemorrhage patients Journal of Science Foundation 2019;17(1):9-14